A novel approach of neoadjuvant and adjuvant therapy with surgery for large keloids of the ear - Sivakumar S; Thenmozhi MD; Sethuraja K; Ashwin Raja A (Asian Journal of Medical Sciences, 2023)
Background: Ear keloids form after ear piercing in genetically predisposed young adults, causing cosmetic disfigurement and negative psycho-social impact, and reducing quality of life. Total excision of ear keloids leads to loss of ear tissue distorting ear framework and reconstruction to restore esthetically pleasant ear causes scarring and more aggressive keloids. Rate of recurrence is higher than 80% when surgical excision alone is done. Aims and Objectives: The study was conducted to compare the efficacy of intralesional triamcinolone acetonide (TAC) or 5-fluorouracil (5 FU) as monotherapy, combined TAC+5 FU and multi-modal therapy (TAC+5 FU+surgical excision) for keloids of the ear. Materials and Methods: The prospective comparative study included 30 patients who presented to the out-patient clinic of plastic surgery department of Government Mohan Kumaramangalam Medical College Hospital, Salem for a duration of 2 years from January 2021 to December 2022. Patients were categorized into three groups based on size of ear keloids, Group I (10) – Injection TAC (A) or 5- FU (B), Group II (10): Injection TAC+5-FU, and Group III (10): Injection TAC+5- FU+Surgical excision (A – neoadjuvant+adjuvant; B – only adjuvant). Results: Of a total of 30 patients, Group IIIA showed significant reduction of keloid with least side effects, most pleasing cosmetically (Patient and observer scar assessment scale 1/10). No recurrence in follow up. Conclusion: Multi-modal therapy consisting of neoadjuvant TAC+5-FU, surgical excision, and adjuvant TAC+5 FU offers the best long-term results for large ear keloids.